Fundamental Questions : Gender Dimensions in Max Planck Research Projects - Weber, Ulla; Weber, Ulla (Baden-Baden)
For the first time, the Max Planck Society is publishing an anthology on gender research, "Fundamental Questions". Thanks to the broad spectrum of disciplines and cultures represented in the Research Association, the authors, who come from various institutes, present their findings in numerous fields of research: law, art history, history of science, neuroscience and computer science. The approaches, topics, issues and methodology of the collected contributions are equally diverse. This diversity shows in the best possible way that the integration of the gender perspective is beneficial not only for applied science and development, but also for basic research. With contributions by Dr. Laura A. Bechthold, Elifcan Celebi, Dr. Marina Chugunova, Dr. Luisa Stella de Oliveira Coutinho Silva, Svenja Friess, Ph.D. Giorgia Gastaldon, Dr. Lisa Hanstein, Dr. Philine Helas, Prof. Karin Hoisl, Ph.D. Michael E. Rose, Esra Sarioglu, Isabel Valera and Dr. Ulla Weber.
For the first time, the Max Planck Society is publishing an anthology on gender research, "Fundamental Questions". Thanks to the broad spectrum of disciplines and cultures represented in the Research Association, the authors, who come from various institutes, present their findings in numerous fields of research: law, art history, history of science, neuroscience and computer science. The approaches, topics, issues and methodology of the collected contributions are equally diverse. This diversity shows in the best possible way that the integration of the gender perspective is beneficial not only for applied science and development, but also for basic research. With contributions by Dr. Laura A. Bechthold, Elifcan Celebi, Dr. Marina Chugunova, Dr. Luisa Stella de Oliveira Coutinho Silva, Svenja Friess, Ph.D. Giorgia Gastaldon, Dr. Lisa Hanstein, Dr. Philine Helas, Prof. Karin Hoisl, Ph.D. Michael E. Rose, Esra Sarioglu, Isabel Valera and Dr. Ulla Weber.
English
Keywords: LAQ,JFSJ